The Effect of Flexible Working Arrangement Applies During the Pandemic Period on Employees Job Satisfaction and Motivation: A Field Research - Yıldırım, Özlem; Tengilimoğlu, Dilaver (Fırat University, 2022)
The pandemic has had certain negative influences on businesses and employees alike. In order to reduce these negative effects, transition to a flexible working system is one of a major expedient taken by both public and private enterprises. This study was performed in order to depicture how the flexible working system affects the motivation and job satisfaction of the employees. Target population of the study consists of individuals working in the additional building of a municipality in Ankara and individuals working in a private dormitory. In order to achieve a significant data acquisition, the survey method was referred and 340 people were reached for the questionnaire. The received answers were analysed by SPSS program and the study reached critical conclusions which were explicated by charts. As a result of the research, job satisfaction of public employees was ascertained to be higher than that of private sector employees. Abstractively, a positive correlation between flexible working and job satisfaction (0.193), and a positive correlation between flexible working and job motivation (0.193) were determined. Yet another important result was a determination which indicates a positive relationship between employee motivation and job satisfaction (0,502).

Covid-19 pandemisi ile beraber işletmeler hem varlığını sürdürmek hem de salgının yayılmasının önlenmesi amacıyla bir dizi önlem almak durumunda kalmışlardır. Hem kamu hem de özel işletmelerin olumsuz etkileri azaltmak adına aldıkları önlemelerden birisi de esnek çalışma sistemine geçişleri olmuştur. Esnek çalışma sisteminin çalışanların motivasyonu ve iş doyumu üzerinde nasıl bir etki yarattığını belirlemek amacıyla bu çalışma gerçekleştirilmiştir. Çalışma evrenini Ankara daki bir belediyenin ek binasında çalışan bireyler ile bir özel yurtta çalışan bireyler oluşturmaktadır. Veri toplama tekniği olarak anket yönteminden yararlanılmış ve 340 kişiye ulaşılmıştır. Anketin birinci bölümünde esnek çalışma düzenlemesine yönelik sorular, ikinci bölümde Minnesota iş doyumu ölçeğinin kısa formu, üçüncü kısımda ise motivasyon soruları yer almaktadır. Verilen cevaplar SPSS programıyla analiz edilmiş ve bulgular tablolaştırılarak yorumlanmıştır. Araştırma sonucunda kamu çalışanlarının iş doyumu özel sektör çalışanlarının iş doyumuna göre daha yüksek bulunmuştur. Ayrıca esnek çalışma ile iş doyum düzeyi arasında pozitif (0, 273), esnek çalışma ile iş motivasyon arasında da pozitif yönlü bir ilişki ( 0,193) bulunmuştur. Önemli bir sonuç da çalışan motivasyonu ile iş doyumu arasında pozitif bir ilişki saptanmıştır( 0,502).
PANDEMİ SÜRECİNDE UYGULANAN ESNEK ÇALIŞMA DÜZENLEMESİNİN ÇALIŞAN MOTİVASYONU VE İŞ DOYUMUNA ETKİSİ; BİR ALAN ARAŞTIRMASI